Outcomes of Renal Transplantation in Brunei Darussalam over a Twenty-Year Period (1993–2012). (12th November 2014) - Tan, Jackson; Khalil, Muhammad Abdul Mabood; Tan, Si Yen; Khalil, Muhammad; Ahmed, Dalinatul; Zinna, Shaukat; Chong, William
Abstract : Objectives . Brunei Darussalam has a high prevalence and incidence of end stage renal disease (ESRD). Up until 2012, all renal transplantations were performed in overseas centres, either as government-sponsored (living-related transplantation) or as self-sponsored (commercialized transplantation) ones. We hypothesize that graft and patient survival of Brunei renal transplant patients are on a par with international standards. Materials and Methods . Data of all renal transplant patients in Brunei were analysed over a twenty-year period from registry records and case notes. Comparative survival data from other countries were obtained from PubMed-listed literature. Results . A total of 49 transplantation procedures were performed in foreign centres between 1993 and 2012. 29 were government-sponsored and 20 were self-sponsored transplantations. The 5- and 10-year overall patient survival rates were 93.3% and 90.1%, respectively. The 5- and 10-year overall graft survival rates were 91.1% and 81.2%. There is no difference in the survival outcomes of government-sponsored and self-sponsored patients. Living-related (government-sponsored) and commercialised (self-sponsored) grafts had equivalent survival to those reported in the literature. Conclusion . Our survival data was on par with those achieved in many countries. We hope to use this information to convince local stakeholders and patients to favour transplantation as the preferred modality of RRT.